Seasonal Variability of Waves Within the Indonesian Seas and Its Relation With the Monsoon Wind - Purwanto Purwanto; Denny Nugroho Sugianto; Muhammad Zainuri; Galuh Permatasari; Warsito Atmodjo; Baskoro Rochaddi; Aris Ismanto; Parichat Wetchayont; Anindya Wirasatriya (Marine Science Department Diponegoro University, 2021)
The previous studies have simulated the variability of the wave within the Indonesian seas which showed that the variability of wave follows the seasonal pattern. However, their analysis only consider the influence of local wind forcings. The bias and error of their simulated wave were also unclear. In the present study, we investigate the variability of wave within the Indonesian seas and its relation with the surface wind speed using the combination of reanalysis and remote sensing data with high accuracies. We split the analysis into swell and wind wave to obtain the influence of local and remote wind forcings. We show that at the inner seas (i.e., the South China Sea, Java Sea, Flores Sea, Banda Sea and Arafura Sea), the variability of significant wave height (SWH) is majorly influenced by the variability of the speed of monsoon wind. The maximum SWH during Northwest monsoon (NWM) season is located at the South China Sea while during Southeast monsoon (SEM) season is at Arafura Sea. This indicates that the wind wave (sea) is dominant at the inner seas. At the open seas (i.e., Pacific Ocean and Indian Ocean) the variability of SWH less corresponds to the the speed of monsoon wind. The remote wind forcings control the wave variability in the open ocean area. This indicates that swell is dominant at the open seas. In general, the magnitude of SWHswell is also more than SWHsea within the Indonesian seas.